Gross Regional Domestic Product and Rice Production: Determinants of Farmer Welfare in Java - Rizki Khairani Hasibuan; Aradea Margareta; Aulia Biea Bellia; Melliani Septiawati; Amelia Indah Putri Cahyani; Ahmad Setiawan Nuraya (Institut Teknologi dan Bisnis (ITB) Semarang, 2026)
The purpose is to analyze the effects of Gross Regional Domestic Product (GRDP) and Rice Production (RP) on Farmers’ Terms of Trade (FTT) as a proxy for farmers’ welfare in East Java, Central Java, and West Java. This research method use a quantitative approach was employed using panel data consisting of 42 observations from three provinces over the period from the first quarter of 2022 to the second quarter of 2025. Secondary data were obtained from Statistics Indonesia (BPS) and analyzed using panel data regression with EViews 12. Model selection was conducted through the Chow, Hausman, and Lagrange Multiplier tests, followed by hypothesis testing using the t-test, F-test, and coefficient of determination (Adjusted R²). The results reveal that GRDP has a positive and significant effect on FTT (β = 58.268; p < 0.05), indicating that regional economic growth contributes to improving farmers’ welfare. In contrast, rice production has a negative but insignificant effect on FTT (β = -0.229; p > 0.05), suggesting that increased production alone does not necessarily improve farmers’ welfare due to factors such as price fluctuations and production costs. Simultaneously, the model is statistically significant and explains 88.28% of the variation in FTT. That policies aimed at improving farmers’ welfare should not focus solely on increasing agricultural production but should also promote inclusive regional economic growth, price stabilization, and efficient agricultural marketing systems. Future studies are encouraged to incorporate additional variables and broader geographical coverage to provide a more comprehensive understanding of the determinants of farmers’ welfare.